Climate change and the future of the Norwegian alpine ski industry. Issue 19 (1st October 2020) - Scott, Daniel; Steiger, Robert; Dannevig, Halvor; Aall, Carlo
ABSTRACT: The demand for foresight on how climate change will alter the competitiveness of ski destinations continues to increase. Norway is often considered the country where modern skiing began, yet its climate change risk remains largely unknown. The SkiSim2 model is run with RCP 4.5 and 8.5 emission climate futures to analyse implications for ski season at 110 alpine ski areas in Norway in the 2030s, 2050s, and 2080s with only natural snow and with advanced snowmaking. A considerable shortening of the ski season in projected as early as the 2030s for the half of ski areas that currently lack snowmaking. Naturally snow reliable ski areas decline from approximately half in the 2030s to a third in the 2050s. With snowmaking, ski season losses are substantially reduced and the majority of ski areas remain snow reliable until the end of the twenty-first century in a lower emission future. A substantial shortening of the ski season (up to 40 days) nonetheless begins in the 2050s under a high emission scenario. The need to invest in snowmaking will continue to increase, with attendant financial and sustainability implications. The differential climate risk among five regions of Norway and the European Alps is also discussed.